2020
DOI: 10.1055/a-1100-7066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Molecular, Functional, and Structural Characterization of CYP17A1 Mutations in Brazilian Patients with 17-Hydroxylase Deficiency

Abstract: Abstract17-Hydroxylase-deficiency (17OHD) is a rare form of congenital adrenal hyperplasia. The aim of the work was to study clinical, biochemical, and the follow up of 17OHD patients and evaluate the function and structure of CYP17A1 mutations. Brazilian patients (three 46, XX and four 46, XY; 17±1.9 years) with combined 17-hydroxylase/17,20-lyase deficiency were evaluated. CYP17A1 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…described that more than 90% of patients with 17OHD received up to two incorrect diagnoses before the final diagnosis, confirming that 17OHD remains highly underdiagnosed ( 31 ). More than 130 mutations have been detected thus far, but W406R is the most prevalent in Brazil (50%), followed by R362C (approximately 30%) ( 32 34 ). HT starts during infancy and is difficult to control, predisposing patients to early renal and cardiovascular outcomes.…”
Section: Deoxycorticosterone As a Key Player ( Table 1 ...mentioning
confidence: 99%
“…described that more than 90% of patients with 17OHD received up to two incorrect diagnoses before the final diagnosis, confirming that 17OHD remains highly underdiagnosed ( 31 ). More than 130 mutations have been detected thus far, but W406R is the most prevalent in Brazil (50%), followed by R362C (approximately 30%) ( 32 34 ). HT starts during infancy and is difficult to control, predisposing patients to early renal and cardiovascular outcomes.…”
Section: Deoxycorticosterone As a Key Player ( Table 1 ...mentioning
confidence: 99%
“…Among these CAH forms, 17OHD is exceptionally rare, accounting for approximately 1% of all CAH cases with an incidence rate of approximately 1:50,000-100,000 [3]. Previous studies have demonstrated that mutations in cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1), located on chromosome 10, contribute to the manifestation of 17OHD [4] and CYP17A1 consists of 508 amino acids, including eight exons and seven introns [5]. The gene encoding for cytochrome P450c17 ex-presses the activities of both 17α-hydroxylase and 17,20lyase [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in CYP17A1 result in complete 17α-OHD or partial 17α-OHD [3]. The typical clinical manifestations of 17α-OHD are sexual naivety, with vague or feminine apparent de nition of the external genitalia; pubescent and adult females present with no pubertal development and primary amenorrhea, and males show vulval dysplasia or femininity [2,4]. Adrenocorticotropic hormone (ACTH) is compensated at a high level, which stimulates the excessive secretion of 11-deoxycorticosterone (11-DOC) and corticosterone (B), causing increased extracellular volume, hypokalaemia, and hypertension [2,5].…”
Section: Introductionmentioning
confidence: 99%